Intrathecal administration of autologous bone marrow stromal cells improves neuropathic pain in patients with spinal cord injury. (23rd March 2018) - Vaquero, J.; Zurita, M.; Rico, M.A.; Aguayo, C.; Fernández, C.; Gutiérrez, R.; Rodríguez-Boto, G.; Saab, A.; Hassan, R.; Ortega, C.
Highlights: Treatment of Neuropathic Pain (NP) is extremely difficult. Cell therapy for NP has been considered in basis to preclinical studies. We present clinical evidence of NP relief after intrathecal Mesenchymal Stem Cells administration. The possibility of cell therapy for pain refractory to conventional treatments should be considered. Abstract: Neuropathic pain (NP) is highly disabling, responds poorly to pharmacological treatment, and represents a significant cause of decreased quality of life in patients suffering from spinal cord injury (SCI). In recent years, cell therapy with autologous mesenchymal stromal cells (MSCs) has been considered as a potential therapeutic weapon in this entity. Ten patients suffering chronic SCI received 100 million MSCs into subarachnoid space by lumbar puncture (month 1 of the study) and this procedure was repeated at months 4 and 7 until reaching a total doses of 300 million MSCs. Intensity of NP was measured by standard numerical rating scale (VAS) from 0 to 10, recording scores previous to the first MSCs administration and monthly, until month 10 of follow-up. Months 1, 4, 7 and 10 of the study were selected as time points in order to a statistical analysis by the nonparametric Wilcoxon rank test. Our results showed significant and progressive improvement in NP intensity after the first administration of MSCs (p: 0.003). This study supports the benefit of intrathecal administration of autologous MSCs for the treatment of NP in patients with SCI.